2018
DOI: 10.3399/bjgp18x695753
|View full text |Cite
|
Sign up to set email alerts
|

Improving palliative care provision in primary care: a pre- and post-survey evaluation among PaTz groups

Abstract: Implementation of PaTz improved systematic identification of palliative care patients within the GP practice. Use of the PaTz register has added value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 16 publications
1
19
0
7
Order By: Relevance
“…The PaTz groups are teams consisting of GPs and community nurses, who, supervised by a physician with expert training in palliative care, discuss their palliative patients five to six times a year. 35 Furthermore, multidisciplinary team meetings were mentioned, such as interdisciplinary consultation and moral case deliberation. Ethical discussions or moral deliberation services are not easily available and accessible in primary care in the Netherlands, hence they may be unaware of these options.…”
Section: Resultsmentioning
confidence: 99%
“…The PaTz groups are teams consisting of GPs and community nurses, who, supervised by a physician with expert training in palliative care, discuss their palliative patients five to six times a year. 35 Furthermore, multidisciplinary team meetings were mentioned, such as interdisciplinary consultation and moral case deliberation. Ethical discussions or moral deliberation services are not easily available and accessible in primary care in the Netherlands, hence they may be unaware of these options.…”
Section: Resultsmentioning
confidence: 99%
“…PaTz-participants feel that PaTz improves collaboration, while strengthening participants' expertise and providing emotional support [15], and PaTz is associated with improved communication, both between healthcare providers and with patients [18]. The PaTz-register seems a crucial element in PaTzgroups, as compared to patients who are not on the register, the preferred place of death is more often known for patients who are on the register, who also are less often admitted to the hospital in the final month [19]. In addition, their death is anticipated earlier by their GP, treatment is aimed at palliation earlier and they more often have conversations on end of life topics, like life expectancy and palliative care treatment options [19].…”
Section: Introductionmentioning
confidence: 99%
“…The PaTz-register seems a crucial element in PaTzgroups, as compared to patients who are not on the register, the preferred place of death is more often known for patients who are on the register, who also are less often admitted to the hospital in the final month [19]. In addition, their death is anticipated earlier by their GP, treatment is aimed at palliation earlier and they more often have conversations on end of life topics, like life expectancy and palliative care treatment options [19].…”
Section: Introductionmentioning
confidence: 99%
“…In palliative care, patients’ desire for information has been shown to contrast with a failure by physicians to predict prognosis. 12 , 14 , 15 Studies have also shown that even if they are able to predict poor prognosis, GPs and HPs are reluctant to discuss poor prognosis and preferences regarding related treatment and care with patients and their relatives. 16 21 Other studies have identified deficits in information exchange and communication between physicians, including those working in different care settings.…”
Section: Introductionmentioning
confidence: 99%